(untitled) (Journal of NELTA, 2023)
Amidst the escalating emergence of generic methodological articles on narrative inquiry, this article critically reviews diff erent narrative analysis approaches and their application in English language teachers’ professional identity research. For this purpose, we reviewed currently available methodological books and articles on narrative inquiry in general and narrative analysis in particular. Additionally, we reviewed twenty purposively selected empirical articles published since 2015 thatemployed narrative inquiry to explore English teachers’ professional identities. A review of methodological articles revealed that the narrative analysis and analysis of narrative dichotomy are blurred as a certain level of interpretation occurs during the co-construction of stories, transcribing, translating, restorying, and fi nally, the consumption of the reports by the readers. Consequently, many researchers have considered paradigmatic analysis as the first step of narrative analysis. In contrast, research practices showed that the interpretation of stories begins only after story generation. Besides, amongst diff erent narrative analysis approaches, positioning analysis underscores how tellers represent themselves through narratives, whereas the small story approach of Barkhuizen accentuates analyzing content and context; however, narrative forms and linguistic features and their motives are rarely investigated. Though the small stories approach of Georgakopoulou (2007) advocates explicitly for considering ways of telling (linguistic features and communicative how), it is rarely evident in practice. This article, therefore, identifies a need for a comprehensive narrative analysis approach that considers what (content), where and when (context), how (form), and who and why (agency and discourse) of the story.